Film boiling suppression and boiling heat transfer enhancement by dielectrophoretic effect - Nguyen, Thien-Binh (2023)
Two-phase heat transfer is one of the most efficient methods for heat dissipation for heated surfaces. However, there is an operational limit called film boiling for any heated surface whereby high surface temperature generates sufficient vapor to form a steady vapor film that both covers the heated surface and drastically reduces the heat dissipation rate. In this study, we introduce a novel approach using the dielectrophoretic effect to suppress the film boiling behavior and enhance the heat transfer rate. We experimentally characterize the transition from film boiling to nucleate boiling caused by the dielectrophoretic effect. We also experimentally determine the dependence of heat transfer enhancement and the associated surface temperature decrease on the applied voltage used to induce the dielectrophoretic effect. We demonstrate that for a smooth surface, activating the dielectrophoretic effect leads to an enhancement in critical heat flux up to 200% within our explored range of applied voltage.